2023
DOI: 10.3390/genes14030686
|View full text |Cite
|
Sign up to set email alerts
|

Optical Genome Mapping Reveals and Characterizes Recurrent Aberrations and New Fusion Genes in Adult ALL

Abstract: (1) Background: In acute lymphoblastic leukemia (ALL) the genetic characterization remains challenging. Due to the genetic heterogeneity of mutations in adult patients, only a small proportion of aberrations can be analyzed with standard routine diagnostics. Optical genome mapping (OGM) has recently opened up new possibilities for the characterization of structural variants on a genome-wide level, thus enabling simultaneous analysis for a broad spectrum of genetic aberrations. (2) Methods: 11 adult ALL patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 48 publications
2
9
0
1
Order By: Relevance
“…As mentioned before, OGM's utility has also been explored by many other groups in different conditions and has demonstrated excellent results and concordance with traditional cytogenetic analysis [2,4,5,7,9,[21][22][23]. For example, in a clinical validation study in which 92 sample runs were included (belonging to 69 samples, 59 hematological neoplasms and 10 healthy controls), OGM showed a sensitivity of 98.7%, specificity of 100% and an accuracy of 99.2% in comparison to standard techniques (karyotype analysis, FISH, and chromosomal microarray), with a 100% first-pass rate regarding the quality control metrics [2].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…As mentioned before, OGM's utility has also been explored by many other groups in different conditions and has demonstrated excellent results and concordance with traditional cytogenetic analysis [2,4,5,7,9,[21][22][23]. For example, in a clinical validation study in which 92 sample runs were included (belonging to 69 samples, 59 hematological neoplasms and 10 healthy controls), OGM showed a sensitivity of 98.7%, specificity of 100% and an accuracy of 99.2% in comparison to standard techniques (karyotype analysis, FISH, and chromosomal microarray), with a 100% first-pass rate regarding the quality control metrics [2].…”
Section: Discussionmentioning
confidence: 92%
“…OGM is being increasingly implemented in cytogenetics laboratories and its use has been explored in diverse settings, including prenatal or postnatal constitutional studies, solid tumors, and diverse hematologic malignancies [3][4][5][6][7][8][9][10]. However, to our knowledge, there are no reports about its applicability in BMFSs to date.…”
Section: Introductionmentioning
confidence: 99%
“…No change Intensified Downgraded AML (25) 18 (72%) 7(28%) 0 ALL (17) 13 (76.47%) 4 (23.52%) 0 CLL (4) 3 (75%) 1 (25%) 0 MPN (15) 15 (100%) 0 0 MDS (5) 4 (80%) 1 (20%) 0 MPN/MDS (4) 3 (75%) 1 (25%) 0 MPAL (5) 5 (100%) 0 0 Multiple myeloma (8) 8 (100%) 0 0 Lymphoma (11) 11 (100%) 0 0 Total (94) 80 14 0…”
Section: Diagnosismentioning
confidence: 99%
“…Concordance to standard clinical testing methods was published for multiple hematological malignancies [11,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Levy and colleagues published a deep dive multisite study of acute myelogenous leukemia (AML) where they revealed that OGM was 100% concordant with karyotyping and FISH and detected additional clinically relevant abnormalities missed by standard tests in 13% of cases [15].…”
Section: Introductionmentioning
confidence: 99%
“…At our tertiary care center, OGM has been implemented in parallel to routine clinical cytogenetic testing to evaluate its feasibility in acute leukemias, as described previously [23,28,30,31]. Written and informed consent was provided for patient participation in this study and for publication.…”
Section: Patient Consentmentioning
confidence: 99%